Characteristics and Outcome of Patients Diagnosed With HIV at Older Age. Issue 1 (January 2016) - Asher, Ilan; Guri, Keren Mahlab; Elbirt, Daniel; Bezalel, Shira Rosenberg; Maldarelli, Frank; Mor, Orna; Grossman, Zehava; Sthoeger, Zev M.
Abstract : Abstract: To characterize the clinical, virological, and immunological status at presentation as well as the outcome of patients diagnosed with HIV above the age of 50. A retrospective study of 418 patients newly diagnosed with HIV in 1 Israeli center, between the years 2004 and 2013. Patients with new HIV diagnosis ≥50 years of age defined as "older" and <50 defined as "younger." Patients were evaluated every 1 to 3 months (mean follow-up 53 ± 33 months). Patients with <2 CD4/viral-load measurements or with <1 year of follow-up were excluded. Time of HIV infection was estimated by HIV sequence ambiguity assay. Ambiguity index ≤0.43 indicated recent (≤1 year) HIV infection. Eighty nine (21%) patients were diagnosed with HIV at an older age. Those older patients presented with significant lower CD4 cell counts and higher viral-load compared with the younger patients. At the end of the study, the older patients had higher mortality rate (21% vs 3.5%; P < 0.001) and lower CD4 cell counts (381 ± 228 vs 483 ± 261cells/μL; P < 0.001) compared with the younger patients. This difference was also observed between older and younger patients with similar CD4 cell counts and viral load at the time of HIV diagnosis and among patients with a recent (≤1 year) HIV infection. One-fifth of HIV patients are diagnosed at older age (≥50 years). Those older patients have less favorable outcome compared with the younger patients. This point to the need of educational and screening programs within older populations and for a closer follow-up of older HIV patients.